Analysis of the Effectiveness of the Active Role of Communities in Management and Prevention of Forest and Land Fires - Cahyadi, Ade Irwan; Sembiring , Edison; Ramli, Soehatman (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
The South Sumatra Provincial Government encourages community participation in preventing and controlling land and forest fires. Based on this reality, this research aims to find the root of the problem and the factors causing ineffective community participation in preventing and controlling land fires. This type of research is descriptive. The main data in this research was obtained through interviews with sources who know and are involved in efforts to prevent and control land fires and are supported by data from field observation activities. The collected data was then analyzed using triangulation techniques. Selection of policy alternatives in efforts to handle land fires using SWOT analysis. The results of the research show: (1) The frequent occurrence of land fires in Muara Merang Village, Bayung Lencir District, Musi Banyuasin Regency, South Sumatra Province is due to the fact that land is still being prepared by burning it, especially for agricultural activities. seasonal food crops; The land fire that occurred in Muara Merang Village, Bayung Lencir District, Musi Banyuasin Regency, South Sumatra Province was a fire on agricultural land that was left empty, (2) efforts were made to prevent land fires through controlled burning, the establishment of village regulations and community agreements which have proven to be effective preventing land fires; efforts to control land fires have been carried out by the community spontaneously and in mutual cooperation by prioritizing land that has economic potential; So far, community involvement carried out by the government through the formation of Fire Care Groups has not been effective because it is still a formality.